An empirical study of spatial-temporal growth patterns of a voluntary residential green infrastructure program. Issue 8 (3rd July 2018) - Lim, Theodore Chao
Abstract : Voluntary residential green infrastructure (GI) stormwater management retrofit programs can help cities comply with environmental regulations while also improving quality of life. Previous research has identified influential factors in residents' willingness to adopt GI, but few have simultaneously studied the spatial and temporal dynamics of GI. I use a six-year record of participation in a voluntary residential GI program in Washington DC to explore how neighborhood characteristics and social influence affect GI adoption over time. Statistical regression and Monte Carlo permutation resampling techniques are used to explain the spatial-temporal patterns of growth of the program. I demonstrate empirical evidence that participation location is increasingly determined by the locations of previous participants. These findings suggest that past participants will increasingly influence spatial clustering of GI in the city.